Utvärdering av berikning till röd vari (Varecia rubra) - Hansell, Madeleine (SLU/Dept. of Animal Environment and Health (until 231231), 2018)
The red ruffed lemur is endemic to Madagascar and classifies as a critically endangered species. It naturally lives in the canopy of the rainforest and is the most frugivorous lemur of Madagascar. Suspensory feeding postures are common to enable harvesting from small branches.